Formação em Saúde da Mulher do profissional Técnico em enfermagem: contribuições de uma abordagem problematizadora - (:unkn) unknown (Universidade Federal do Pampa, 2022)
The present research aims to understand what is shown about the pedagogical approaches in the training of mid-level nursing technicians who work in Women's Health in educational establishments in the state of Rio Grande do Sul.Of the one hundred and twenty institutions that offer mid-level technical training in nursing in the state, twenty-five coordinators of a technical course in nursing and sixteen professors participated in the research. As an instrument for obtaining information, a questionnaire was used through Google forms. Data were submitted to Discursive Textual Analysis (MORAES; GALIAZZI, 2016). The results pointed to a pedagogical approach that still maintains the fragmented vision of Women's Health, strongly associating Women's Health with care during pregnancy, childbirth and the puerperium. As much as public policies related to Women's Health are addressed, as proposed by the National Catalog of Technical Courses, what remains is the technicality associated with care, not taking into account other activities that the nursing technician can also develop as part of team at UBS. It is worth noting that some of the pedagogical approaches of these teachers are carried out through activities developed by the teachers who emphasize the contextualization of reality and the students' experiences as a methodological tool leading to reflection, and leading to a critical/problematic approach. In this way, it leads us to argue that these are promising for the training of health professionals capable of identifying problems, raising hypotheses, and pointing out possible solutions to the problems of the local reality. The systematization of the results allowed the elaboration of a practical theoretical essay that constitutes a viable possibility to be inserted in the pedagogical practice of teachers and professors who train technicians in Nursing at medium level with a problematizing approach, and its elaboration is the result of several studies both from the theoretical framework of the problematizing approach via Maguerez's arch, the principles of training for Women's Health and technical training at a secondary level in nursing. Finally, it is argued that this is a promising methodology, which is in line with what the legislative documents for Technical Vocational Education at Middle Level and the Unified Health System advocate.
Keywords: Saúde da mulher; Técnico em enfermagem; Arco de Maguerez; Women's health; Nursing technician; Arch of Maguerez; CNPQ::CIENCIAS HUMANAS